GREEN MARKETING: STRATEGY FOR GAINING SUSTAINABLE COMPETITIVE ADVANTAGE IN INDUSTRY 4.0 - Ika Purwanti; Muhammad Dzikri Abadi; Umar Yeni Suyanto (Manajemen Bisnis, 2019)
This study would like to explains conceptual green marketing and its role as a source sustainable competitive advantage in industrial revolution 4.0. The environmental issue is a sizzling topic nowadays as almost every country’s government and society has started to be more aware of these issues. Plus, there is currently a phenomenon of industrial revolution 4.0 which demands business practices to be more consumer-oriented. Public concern over environmental damage has made marketers know the needs and value of environmentally friendly marketing, namely green marketing. which is a new strength to create a sustainable competitive advantage. This study is a library research gathering and analyzing information from related references and theories, which have become the basic foundation and sources in analyzing problems in this research. This study seeks to offer Green Marketing ideas as the latest approach in dealing with various business threats. The results show that green marketing able to encourage companies to prepare themselves faster and better, the definition of green marketing has changed over time according to the growing relevance of environmental sustainability.